Understanding the Effects of Novel Engineering Targets on Sugar Sensing in S. cerevisiae - Fjölnisdóttir,Birta Líf (2018)
Baker´s yeast S. cerevisiae has been engineered in order to enable xylose uptake and utilization from lignocellulosic biomass as this yeast cannot naturally metabolize this pentose sugar. However, xylose is not recognized as a fermentable sugar by S. cerevisiae and recent studies on the effect of xylose on the three main sugar signaling pathways (Snf3p/Rgt2p, SNF1/Mig1pt and cAMP/PKA) have indicated that S. cerevisiae cannot sense extracellular xylose. In parallel, it was recently shown that the combined deletions of HOG1, IRA2, GRE3 and ISU2 gave epistatic interactions resulting in improved growth and xylose uptake in recombinant S. cerevisiae strains containing the XI pathway. The objective of the present study was to explore the effects of those gene deletions on sensing and signaling for the three sugar signaling pathways. Deletions of IRA2, ISU1 and HOG1 were constructed in S. cerevisiae strains containing the XR-XDH pathway as well as a biosensor for each of the signaling pathways and the response was recorded using flow cytometry. Results confirmed clear effects of the deletions on all the signaling pathways, with ira2Δ mutants mimicking high glucose signal with constitutive activation of PKA and hog1Δ mutants giving low glucose responses. When combined with the deletion of ISU1, the SNF1/Mig1p pathway was clearly affected since subpopulations were alleviated.
Keywords: S. cerevisiae; yeast; sugar signaling; Snf3p/Rgt2p; SNF1p/Mig1p; cAMP/PKA; xylose; sustainability; flow cytometry; biosensor; applied microbiology; teknisk mikrobiologi